Oral health status and treatment needs of children with sensory deficits in Chennai, India-A cross-sectional study - P Vishnu; R Mahesh; P D Madan Kumar; N Sharna (Wolters Kluwer Medknow Publications, 2021)
Purpose: The negligence of oral health combined with barriers in accessing adequate oral care is more commonly encountered in children with sensory deficits. In a developing country like India, there is a severe lacuna in data regarding the oral health status and treatment needs in this group of population. The purpose of this study is to assess the oral health status and treatment needs of children with sensory deficits, using WHO criteria of Basic Oral Health Survey Methods, 1997. Materials and Methods: A descriptive cross-sectional study was conducted using the WHO criteria (Basic Oral Health Survey, 1997); questionnaire data regarding the demographic profile, oral hygiene status, degree of sensory impairment were recorded and tabulated. The Chi-square test was used to determine whether there existed a significant difference in the oral health status. The confidence interval was set at 95% and alpha error was assumed at 0.05. Results: Among the 742 sensory deficit children examined, 371 children are visually impaired and 371 are hearing impaired. Gingival bleeding and poor oral hygiene is diagnosed in more than 70% of the visually impaired children. The prevalence of trauma is estimated to be 8% in children, who are visually impaired. In the hearing impairment group, gingival bleeding because of inadequate oral hygiene is seen in 58% of the population examined. There is no statistically significant difference in the dental caries status between visually impaired and hearing impaired children (P > 0.05). There is also no statistically significant difference in the restorative treatment need and trauma status between visually impaired and hearing impaired children (P > 0.05). Conclusion: The present study shows a high prevalence of gingival diseases and dental caries in the special health care group children. The study signifies a wide spread presence of unmet treatment needs among children in this study population.